Effects of soybean 7S protein on the quality and digestibility of dry rice noodles under twin‐screw extrusion process. (8th September 2022) - Qiao, Fan; Wang, Lin; Guan, Chunmin; Long, Xinkang; Lin, Qinlu; Liu, Chun
Summary: Starch and protein are important components of food, the mixed system formed between them (complexes, gels, mixtures, etc.) can improve the physical and chemical properties of starch and protein, and its potential application in the food industry has also attracted widespread attention. In this study, indica rice flour and soybean 7S protein (β‐Conglycinin) were used as the experimental materials to explore the effect of soybean 7S protein addition on the quality and digestibility of rice noodles. Aims to develop rice noodles with high protein and low GI, so that people can take care of their health while satisfying their appetites. The results showed that with the increase of soybean 7S protein addition, the starch digestibility decreased, resulting in the estimated glycaemic index (eGI) and glycaemic load (GL) decreasing. However, the cooking loss rate and breakage rate of rice noodles gradually increased, the water absorption first increased and then decreased, and the taste of rice noodles is acceptable when the 7S protein addition amount is within 9%. The interaction between starch and soybean 7S protein was mediated by weak interactions such as hydrogen bonds and hydrophobic forces indicated by Fourier transform infrared spectroscopy (FTIR) and X‐ray diffraction (XRD). Abstract : Soybean 7S protein can significantly reduce the glycemic index of extruded rice noodles.